Digital Literacy Development Towards Golden Indonesia 2045 - M. Salim; Zudan Rosyidi (Global Action and Education for Society, 2025)
Digital literacy is a form of ability to obtain, understand and use information from various sources in digital form. Digital literacy can help improve the quality of life of the community through increased productivity, efficiency, and innovation. Mastery of literacy in all aspects of life is indeed a fundamental thing in the progress of a nation's civilization. The Vision of Golden Indonesia 2045 is an idea where in 2045 Indonesia will experience progress with rapid development where the momentum also coincides with the 100th anniversary of Indonesian independence. This study aims to theoretically describe the findings related to the development of digital literacy towards Golden Indonesia 2045. Literature study is used as a method in this study with a descriptive approach by collecting and reviewing various relevant sources, such as articles, books, and other scientific works that discuss digital literacy and Golden Indonesia 2045. Based on the results of the literature study, various programs were held to improve public literacy. In terms of digital literacy, the government is holding a national literacy movement program to accelerate the digital literacy of the Indonesian people. With several programs that are basically to train and empower Indonesian people's resources in facing global challenges related to the rapid development of digitalization so that they can keep up with the acceleration of the era. This is also inseparable from the role of cooperation between the government and educators, as well as communities that are active in building digital literacy of the Indonesian people in order to prepare for the golden Indonesia 2045. The vision of Golden Indonesia 2045 is an ideal to make Indonesia a Sovereign, Advanced, and Sustainable Country in 2045 when Indonesia celebrates 100 years of independence, to realize this desire is not easy, it requires empowerment of human resources and also innovation in terms of the economy. The government must continue to strengthen the digital literacy of educators through online and offline training and socialization as a form of readiness of educators in following the flow of digitalization and educators are the key to success in the learning process. Digital literacy also plays a key role in encouraging innovation in the field of entrepreneurship.